2021
DOI: 10.1101/2021.07.01.450475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPRa screening with real world evidence identifies potassium channels as neuronal entry factors and druggable targets for SARS-CoV-2

Abstract: Although vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been successful, there are no good treatments for those who are actively infected and potentially suffer from diverse neurological symptoms. While SARS-CoV-2 primarily infects the respiratory tract, clinical evidence indicates that cells from sensory organs, brain, and heart are also susceptible to infection. An understanding of factors critical for viral infection in these tissues may help identify novel therapeutics. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The Severe Acute Syndrome Coronavirus 2 (SARS-CoV-2) spike protein receptor-binding domain, which binds to angiotensin-converting enzyme 2 (ACE2) to initiate viral cell entry, has been shown to contain an exposed RGD motif that has been suggested to be integrin-binding, thus potentially allowing for integrin-mediated cell entry ( Luan et al, 2020 ; Makowski et al, 2021 ). Experimental studies have shown that the SARS-CoV-2 spike protein directly binds α V β 3 and α 5 β 1 integrins and may also interact with α 3 , β 1 , α 4 , and α X integrin subunits ( Aguirre et al, 2020 ; Kotani and Nakano, 2020 ; Beddingfield et al, 2021 ; Nader et al, 2021 ; Wang et al, 2021 ). RGD-based drugs were found to inhibit spike binding to α V β 3 and α 5 β 1 integrins, and mutating the RGD motif to RGE or RGA was also found to decrease binding to α V β 5 integrins – further implicating the spike RGD motif in interactions with integrins ( Sebé-Pedrós et al, 2010 ; Robles et al, 2021 )⁠.…”
Section: Introductionmentioning
confidence: 99%
“…The Severe Acute Syndrome Coronavirus 2 (SARS-CoV-2) spike protein receptor-binding domain, which binds to angiotensin-converting enzyme 2 (ACE2) to initiate viral cell entry, has been shown to contain an exposed RGD motif that has been suggested to be integrin-binding, thus potentially allowing for integrin-mediated cell entry ( Luan et al, 2020 ; Makowski et al, 2021 ). Experimental studies have shown that the SARS-CoV-2 spike protein directly binds α V β 3 and α 5 β 1 integrins and may also interact with α 3 , β 1 , α 4 , and α X integrin subunits ( Aguirre et al, 2020 ; Kotani and Nakano, 2020 ; Beddingfield et al, 2021 ; Nader et al, 2021 ; Wang et al, 2021 ). RGD-based drugs were found to inhibit spike binding to α V β 3 and α 5 β 1 integrins, and mutating the RGD motif to RGE or RGA was also found to decrease binding to α V β 5 integrins – further implicating the spike RGD motif in interactions with integrins ( Sebé-Pedrós et al, 2010 ; Robles et al, 2021 )⁠.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of reported integrin expression levels revealed that several of the putative spike-binding partners are increased during SARS-CoV-2 infection, further adding to their validity. Since a X integrins were both found as putative cell entry receptors for the SARS-CoV-2 spike protein in a CRISPR activation screen, the results presented in this study may help unravel potential binding mechanisms (Wang et al, 2021). The identified motifs may act together with the RGD motif or independently to bind integrins for cell entry or to interfere with cell signaling pathways.…”
Section: Discussionmentioning
confidence: 84%
“…Binding assays demonstrated direct binding between the spike protein and b 1 integrins (Park et al, 2021). A screening of candidate cell entry receptors for SARS-CoV-2 suggested that a 3 and b 1 integrins may be involved, and a CRISPR activation screening looking at neuronal receptors involved in SARS-CoV-2 infection found that a X integrins may mediate cell entry (Kotani and Nakano, 2020;Wang et al, 2021). The antibody natalizumab, which binds to a 4 integrins, was found to decrease SARS-CoV-2 infection, hinting at the potential use of these integrins in cell entry (Aguirre et al, 2020).…”
Section: Integrins and Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations